A Strategy towards the Multigram Synthesis of Uncommon Hexaarylbenzenes. Issue 18 (24th March 2016) - Lungerich, Dominik; Reger, David; Hölzel, Helen; Riedel, René; Martin, Max M. J. C.; Hampel, Frank; Jux, Norbert
Abstract: A novel rational synthetic pathway—the "functionalization of para ‐nitroaniline" (FpNA)—provides substituted hexaarylbenzenes (HABs) with uncommon symmetries that bear up to five different substituents, fully avoiding regioisomeric product distributions during the reactions. 4‐Nitroaniline is functionalized by a cascade of electrophilic halogenations, Sandmeyer brominations, and Suzuki cross‐coupling reactions, leading to 26 substitution geometries, of which 18 structures are not available by the current established techniques. Furthermore, we demonstrate that this method is applicable to the bulk production of such systems on a multigram scale. Regarding optoelectronic properties, we demonstrate how highly functionalized HABs can show strong luminescent behavior, making these molecules very attractive to organic electronic devices. Abstract : Bulk discount on hexaarylbenzenes (HABs): A rational and scalable synthesis of uncommon and highly functionalized HABs utilizes 4‐nitroaniline as the starting material. This approach can potentially provide 18 novel HABs and 26 substitution geometries in total, which are not available or only difficult to obtain by standard techniques.